Analysis of Student Activeness Before the Covid-19 Pandemic and During the Covid-19 Pandemic - Asis T; Wayan Sukarlinawati (Jayapangus Press, 2023)
The learning process has changed globally due to the Covid-19 pandemic that has hit the world. The learning process that used to be carried out face-to-face in the classroom turned into online learning (in the network) due to social restrictions to prevent the spread of the covid-19 virus. The online learning process is assisted by applications such as whatsapp, google classroom, zoom meeting, google meet and other applications. Of course this affects the way of learning and the difficulty of adapting to technology, especially at the elementary school level and has an impact on student activeness in the learning process. Seeing this situation, research is needed to examine this matter. The purpose of this study is to determine student activeness in learning before the COVID-19 pandemic and during the COVID-19 pandemic at UPT SD Negeri 1 Amparita. The method used is descriptive research. The population in the study were all students at UPT SD Negeri 1 Amparita as many as 172 students, while the sample in this study were 89 students with non probability sampling technique. The research data were obtained by distributing questionnaires and supported by activity documentation. The data analysis technique used is quantitative descriptive statistical analysis technique. Based on the results of descriptive analysis, the data obtained shows that student activeness in the learning process before the COVID-19 pandemic at UPT SD Negeri 1 Amparita is more effective than student activeness in the learning process during the COVID-19 pandemic at UPT SD Negeri 1 Amparita.